Analysis of Triple Quantum Dots Single Electron Transistor (TQD-SET) for Various Configuration - Stephanus Hanurjaya; Miftahul Anwar; Meiyanto Eko Sulistyo; Irwan Iftadi; Subuh Pramono (Universitas Sebelas Maret (UNS), 2020)
Single electron transistor (SET) has high potential for the development of quantum computing technologies in order to provide low power consumption electronics. For that purpose, many studies have been conducted to develop SET using dopants as quantum dots (QD). The working principle of SET basically is a single electron tunneling one by one through tunnel junction based on the coulomb blockade effect. This research will simulate various configurations of triple quantum dots single electron transistors (TQD-SET) using SIMON 2.0 with an experimental approach of MOSFET with dopants QD. The configurations used are series, parallel, and triangle configuration. The mutual capacitance (Cm), tunnel junctions (TJ), and temperature values of TQD-SET configurations are varied. The I-V characteristics are observed and analyzed for typical source-drain voltage (Vsd). it is found that the TQD series requires larger Vsd than parallel or triangular TQDs. On the other hands, the current in parallel TQD tends to be stable even though Cm is changed, and the current in the TQD triangle is strongly influenced by the Cm. By comparing these three configurations, it is observed that the tunnelling rate is higher for parallel TQD due to higher probability current moves through three dots by applying Vds.